COMPARATIVE ANALYSIS OF METHODS IN PROBLEMS OF SEISMIC WAVES PROPAGATION IN LAYERED ANISOTROPIC MEDIA - Malytskyy, D.; Pavlova, A. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The theory of seismic wave propagation in anisotropic medium using the matrix method of Thomson-Haskell is presented. The matrix formalism for field displacements on the free surface of an anisotropic layered half-space by introducing the wave propagator is shown. A comparative analysis of the results of our method with the synthetic seismic records obtained by DSM, reflective and FCT methods, and the method of finite differences is shown.